AMENORRHEA IN ELITE ATHLETICS ATHLETES: PREVALENCE AND ASSOCIATIONS TO ATHLETICS INJURY. Issue 7 (11th March 2014) - Rost, M; Jacobsson, J; Dahlström, Ö; Hammar, M; Timpka, T
Abstract : Background: Knowledge is lacking about the associations between sport injuries and components of the female athlete triad. Objective: To assess the prevalence of amenorrhea in elite female athletics athletes and if athletes with history of amenorrhea are at higher injury risk than athletes with regular menstrual cycles or on combined oral contraceptives. Design: Cohort study during a period of 52 weeks. Setting: Swedish female youth and adult elite athletics athletes. Participants: Athletes ranked in the national top-10 in each event were invited to take part in a 52-week surveillance study. Among the female athletes that consented to participate (n=161), 149 (92%) completed a baseline gynecological survey. Risk factor assessment: Amenorrhea, event group, previous injury, training volume and intensity (measured by the TLRI), and interactions with age. Main outcome measurements: Time to first injury causing full or partial time loss from athletics. Results: 37 (25%) athletes reported having history of amenorrhea. More runners reported amenorrhea (P=.017; Cramer's V=0.19) than athletes in the throwing and jumping event groups; this difference in amenorrhea prevalence was distributed to adult runners only (P=.016; Cramer's V=0.26). Additionally, there was a tendency for that runners with a lower BMI had a prevalence of amenorrhea (P=.062). Sixty-six percent of the athletes sustained an injury during the study period. Cox proportional hazards regression analyses did not show statistical associations between amenorrhea and athletics injury. Conclusions: Swedish female athletics athletes reported a high prevalence of amenorrhea compared to the normal population. Athletes with extended exposure to participation in running events with high demands on aerobic performance sufferred more extensively from amenorrhea. No associations with injury incidence could be established, but this finding needs to be confirmed in studies with larger sample size. Further studies of amenorrhea and its health implications among female athletes are warranted.